Common Fixed Point for Two Pairs of Mappings Satisfying (E.A) Property in Generalized Metric Spaces - Wei Long; Mujahid Abbas; Talat Nazir; Stojan Radenović (Abstract and Applied Analysis)
Recently, Abbas et al. (2012) obtained some unique common fixed-point results for a pair of mappings satisfying (E.A) property under certain generalized strict contractive conditions in the framework of a generalized metric space. In this paper, we present common coincidence and common fixed points of two pairs of mappings when only one pair satisfies (E.A) property in the setup of generalized metric spaces. We present some examples to support our results. We also study well-posedness of common fixed-point problem.